Developing a Bilingual Export-Import Handbook for PT Kemira Chemicals Indonesia - Arifananda, Amirah Khadijah (Kirana Publisher (KNPub), 2024)
This research aimed to develop a bilingual handbook for PT Kemira Chemicals Indonesia. To assist companyemployees to deal with difficulties in creating export documents. This research utilized Design andDevelopment Research. Using ADDIE Model, comprising the stage of (Analysis, Design, Development,Implementation, and Evaluation) to create the product of the research. A preliminary study was used tofind content that could help employees. This book is written in two languages, English and Indonesian. Itpresents information on exports and imports, procedures for creating export documents through S4P,calculation notes about Costs, Insurance, Freight, and Incoterms. The product was validated in terms oflanguage and content to improve the quality of the handbook. This research is especially beneficial for PTKemira Chemicals Indonesia in finding solutions to the problems they face, for example, new employees inthe supply chain management division, interns, and obstacles when creating documents through S4P, thisbook can solve the problems that occur.